High-efficiency visible-light-driven Ag3PO4 photocatalysts modified by conjugated polyvinyl alcohol derivatives. (26th February 2020) - Zhu, Xuewang; Shi, Yaxin; Luo, Qingzhi; An, Jing; Yin, Rong; Li, Xueyan; Wang, Desong
Abstract: Due to its high-efficiency Ag3 PO4 serves as a photocatalyst driven by visible light, which in this study was prepared through surface modification using a small amount of conjugated polyvinyl alcohol derivatives (CDPVA) via a simple chemisorption and heat treatment approach. The as-prepared CDPVA/Ag3 PO4 composite photocatalysts were characterized via a varieties of analyses. The photocatalytic performance of the as-prepared composite photocatalysts was estimated through the photodegradation of methyl orange solution and the photoreduction of aqueous Cr(VI) solution with visible light. Results showed that the introduction of a trivial part of CDPVA on the surface of Ag3 PO4 particles did not change their crystallinity and sizes but significantly reduced the aggregation of particles, strengthened the visible-light absorbance, and produced a more efficient separation of the photogenerated electron–hole pairs in the investigated composite photocatalysts. The visible-light photocatalysis of the composites exhibited a higher stability and activity than pure Ag3 PO4 . The visible-light photocatalysis of the composites exhibited an initial rise and a later reduction with increase in CDPVA content in the composites and heat treatment temperature and time. The synthetic photocatalysts exhibited the strongest visible-light photocatalysis when the CDPVA to Ag3 PO4 mass ratio, heat treatment temperature, and treatment time were 1: 8000, 180 °C, and 1 h respectively. The mechanism for visible-light photocatalysis of the CDPVA/Ag3 PO4 composites was also investigated. The solubility of Ag3 PO4 in water environment was significantly decreased by the surface modification of CDPVA.